1986
DOI: 10.1577/1548-8659(1986)115<555:eoudof>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urban Development on Fish Population Dynamics in Kelsey Creek, Washington

Abstract: A 30‐month study of the comparative dynamics of the fish populations inhabiting Kelsey Creek, located in the City of Bellevue, Washington, and a nearby pristine control stream suggest that urban development has resulted in a restructuring of the fish community. Environmental perturbations, including habitat alteration, increased nutrient loading, and degradation of the intragravel environment appeared to have a greater impact on coho salmon Oncorhynchus kisutch and nonsalmonid fish species than on cutthroat tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Scott et al (1986) found that salmonid production was higher at urban sites than forested reference sites in western North America, possibly because invertebrate biomass was greater in the urban stream. In contrast, other North American studies (Onorato et al 2000;Morgan and Cushman 2005) suggest that fish diversity and abundance declines with increasing urbanization, and that relative abundance of tolerant fish taxa increases.…”
Section: Discussionmentioning
confidence: 99%
“…Scott et al (1986) found that salmonid production was higher at urban sites than forested reference sites in western North America, possibly because invertebrate biomass was greater in the urban stream. In contrast, other North American studies (Onorato et al 2000;Morgan and Cushman 2005) suggest that fish diversity and abundance declines with increasing urbanization, and that relative abundance of tolerant fish taxa increases.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of higher temperatures, conductivity and total phosphorus at these sites (Rolla, 2008) may have contributed to an increase in productivity, as also suggested by Treviño et al (1969) and Paul & Meyer (2001) which have shown that nutrient loads can stimulate fish production. In North American streams Scott et al (1986) found that fish grew more rapidly and to larger sizes in urban sites, increasing fish production when compared to forested sites, presumably as a result of warmer temperatures and greater invertebrate biomass in the urban stream.…”
Section: Discussionmentioning
confidence: 99%
“…Scott et al (1986) found that urban development resulted in a restructuring of the fish community, and Pompeu & Alves (2005) and Cunico et al (2006) reported profound changes in fish community structure in two different Brazilian urban rivers. However, despite these few studies on fish assemblage responses to urbanization, a general response model does not exist (Paul & Meyer, 2001), especially for the neotropical region where relevant information is even more scarce.…”
Section: Introductionmentioning
confidence: 99%